Homogenization of dispersal ability across bird species in response to landscape change. Issue 7 (29th December 2016) - Martin, Amanda E.; Desrochers, André; Fahrig, Lenore
Abstract : Human land use is known to homogenize biotic communities, increasing similarity in their genetic, taxonomic and functional diversity. Explanations have focused almost exclusively on human‐mediated extinction and range expansion. However, homogenization could also be produced by land use driving selection for similar traits across species. We propose a novel hypothesis to explain how human land use homogenizes dispersal ability across species. With habitat loss and increasing human land use intensities there should be larger increases in the costs of dispersal for dispersive than sedentary species, because dispersive species interact with non‐habitat more frequently. In contrast, the benefits of dispersal should increase more for sedentary than dispersive species, because sedentary species are at greater risk from inbreeding depression, predation and competition associated with habitat loss. Therefore we predict that sedentary species become more dispersive in a human‐altered landscape, and dispersive species more sedentary. We tested this prediction using wing pointedness to estimate the initial dispersal ability and change in dispersal ability for 21 North American passerines over the 20th century. More pointed wings are associated with stronger dispersal ability. Thus our prediction would be supported by a negative cross‐species relationship between these two measurements. We found a strong, negative relationship, as predicted. This resulted in declines in the variability in wing pointedness among species over time. Although other things can cause wing shape to change, including changes in habitat availability, none of these explained the observed relationship. Our result provides the first evidence that human landscape alteration is homogenizing bird communities, driving selection for intermediate dispersal ability across species. It also implies that more dispersive species are more at‐risk from human landscape use because, when rates of landscape alteration are faster than a species' ability to adapt to that change, the costs of dispersal increase more for dispersive than sedentary species.